2022
DOI: 10.1021/acsami.2c16046
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Colloidal Synthesis of Non-Toxic Electroactive Carbon Dots with a Better Threshold Cytotoxicity and Cytocompatibility

Abstract: Carbon dots (CDs), because of their characteristic size (<10 nm) and highly fluorescent nature, can be internalized in biological cells or can be tagged to the key components of a living system. While these attributes can be potentially exploited for biomedical applications, the toxicity of CDs remains an important issue to be addressed. Both the synthesis approach and morphological attributes critically determine the dose-dependent toxicity and cytocompatibility of CDs. Against this perspective, we report her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…[398] In addition, the cytotoxicity of CDs with different surface modifications has been extensively studied against both animal and human cells. [399][400][401][402] A majority of these studies have suggested that CDs, regardless of surface passivation, do not indicate evidence of toxicity [403] or have identified negligible toxicity [404] when there is great cellular uptake ability that enables easy penetration into cells. An investigation into cellular morphological changes also revealed that CDs conjugated with polymers carrying neutral surface charge do not induce any defined abnormalities in cellular structure and functions when they are used under low concentrations.…”
Section: Cellular Toxicity Of Carbon Dotsmentioning
confidence: 99%
“…[398] In addition, the cytotoxicity of CDs with different surface modifications has been extensively studied against both animal and human cells. [399][400][401][402] A majority of these studies have suggested that CDs, regardless of surface passivation, do not indicate evidence of toxicity [403] or have identified negligible toxicity [404] when there is great cellular uptake ability that enables easy penetration into cells. An investigation into cellular morphological changes also revealed that CDs conjugated with polymers carrying neutral surface charge do not induce any defined abnormalities in cellular structure and functions when they are used under low concentrations.…”
Section: Cellular Toxicity Of Carbon Dotsmentioning
confidence: 99%
“…Carbon dots (CDs) are a type of novel carbon nanoparticle with sp 2 hybridized carbon nanostructures and an average particle size less than 10 nm. 15 CDs have superior luminescence and biocompatibility, making them attractive for biomarkers, nanoscale uorescent probes, and biological imaging applications. [16][17][18] Because CDs contain many carboxylic acid moieties at their surface and can possess variable surface functionalities, microstructures, surface state, and crystalline state, they have a wide range of applications in addition to their use in sensing, drug delivery, environmental pollutant monitoring, diagnosis, and treatment of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of CDs has remained a challenge, with low synthetic yields being a major issue. CDs possess unique properties such as fluorescence, good biocompatibility, and low toxicity, making them useful in many fields such as sensing, imaging, catalysis, , drug delivery, and device applications. CDs have excellent fluorescence ability, and solid-state silane-functionalized CDs can be directly used as phosphors for multicolor light-emitting diodes and all types of white light-emitting diodes .…”
Section: Introductionmentioning
confidence: 99%